PERLINDUNGAN HUKUM TERHADAP KURATOR DALAM MENJALANKAN TUGAS PENGURUSAN DAN PEMBERESAN HARTA PAILIT - Darma Adi Putra, I Made; -, Marwanto; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Curator is a professional that appointed by the Commercial Court to carry outManagement and Settlement of the Bankruptcy estate. When on duty there a lot of obstaclesfounded in the field, that is when a debtor declared bankrupt hence their treasure should bein a general confiscation. However, although it has been decided Bankruptcy by the court,many borrowers who do not cooperate with the existence of the Curator for management ofits company’s property. Another problem have been encountered in performing their duty,that are the Curator reported by the bankrupt debtor to the police. It shows protection to thecurator’s is not yet maximum including related Legal Protection to this profession, there isno clear guarantee to protect the Curator’s duty.
Keywords: Curator, Legal Protection, Management and Settlement, Bankruptcy